2020
DOI: 10.3126/nepjoph.v12i1.24771
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Myocysticercosis different Presentation and Management in Eastern Nepal

Abstract: Introduction: Ocular cysticercosis is a preventable cause of blindness. It is caused by parasitic infestation caused by the larval form of Taenia solium. Poor sanitation and improper management of food and meat products are the major causes for cysticercosis infestation. Case: Two cases of myocysticercosis presented to our hospital differently. A 12 years boy, first case presented with drooping of right eye (RE) upper lid with recurrent swelling, pain, redness with mild headache and intermittent vomiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Cysticercosis is well-known zoonotic disease caused by the parasite of Taenia species. Orbital and adnexal cysticercosis can present with various clinical presentation [ 4 ]. Extraocular muscles are one of the most common lodgment sites of encysted larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Cysticercosis is well-known zoonotic disease caused by the parasite of Taenia species. Orbital and adnexal cysticercosis can present with various clinical presentation [ 4 ]. Extraocular muscles are one of the most common lodgment sites of encysted larvae.…”
Section: Discussionmentioning
confidence: 99%
“…The equal importance of clinical, radiological, microbiological, and histopathological evidence has been suggested by Hamal et al . [ 27 ] for the diagnosis of cysticercosis. In treatment, the steroids have been shown to increase the plasma levels of albendazole, hence, supplementing the therapeutic response of the antihelminthic drug leading to an overall improvement in the outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging modality of choice is B scan ultrasonography (USG) which depicts presence of hyperechoic scolex. [ 4 ] Management remains a challenge for health-care providers due to absence of definitive guidelines. Although medical management is the preferred modality, some authors have reported increased incidence of inflammatory reaction following oral albendazole therapy.…”
Section: Introductionmentioning
confidence: 99%